2021
DOI: 10.14704/web/v19i1/web19001
|View full text |Cite
|
Sign up to set email alerts
|

Modelling an Adaptive Learning System Using Artificial Intelligence

Abstract: The goal of this paper is to use artificial intelligence to build and evaluate an adaptive learning system where we adopt the basic approaches of spiking neural networks as well as artificial neural networks. Spiking neural networks receive increasing attention due to their advantages over traditional artificial neural networks. They have proven to be energy efficient, biological plausible, and up to 105 times faster if they are simulated on analogue traditional learning systems. Artificial neural network libr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Adaptability also includes the ability of higher education institutions to adapt to changes in labor market demands. In an era where job market needs change dynamically, management models must be able to identify these trends and align curricula and educational programs to meet these needs (AL-Fayyadh et al, 2021). AI integration can help in the analysis of job market data, forecast future employment trends, and provide insight into the skills required by graduates.…”
Section: Literatur Of Refiew 1 Adaptive Higher Education Managementmentioning
confidence: 99%
“…Adaptability also includes the ability of higher education institutions to adapt to changes in labor market demands. In an era where job market needs change dynamically, management models must be able to identify these trends and align curricula and educational programs to meet these needs (AL-Fayyadh et al, 2021). AI integration can help in the analysis of job market data, forecast future employment trends, and provide insight into the skills required by graduates.…”
Section: Literatur Of Refiew 1 Adaptive Higher Education Managementmentioning
confidence: 99%
“…AL-Fayyadh et al [31] suggested an approach based on a neural network algorithm to automatically identify the learning style constructed on learners' interactions with the e-learning system. This approach has proven its performance with an accuracy of more than 69.3% on the four learning style dimensions S/G, S/I, A/R, and V/V.…”
Section: K-means Clustering Algorithmmentioning
confidence: 99%